Trophic strategies of intertidal foraminifera explored with single‐cell microbiome metabarcoding and morphological methods: What is on the menu? - Magali Schweizer; Thierry Jauffrais; Constance Choquel; Vona Méléder; Sophie Quinchard; Emmanuelle Geslin (Ecology and Evolution, 2022)
Abstract In mudflats, interactions and transfers of nutrients and secondary metabolites may drive ecosystems and biodiversity. Foraminifera have complex trophic strategies as they often rely on bacteria and eukaryotes or on potential symbionts for carbon and nitrogen resources. The capacity of these protists to use a wide range of adaptive mechanisms requires clarifying the relationships between them and their microbial associates. Here, we investigate the interactions of three foraminiferal species with nearby organisms in situ, by coupling molecular (cloning/Sanger and high‐throughput sequencing) and direct counting and morphological identification with microscopy. This coupling allows the identification of the organisms found in or around three foraminiferal species through molecular tools combined with a direct counting of foraminifera and diatoms present in situ through microscopy methods. Depending on foraminiferal species, and in addition to diatom biomass, diatom frustule shape, size and species are key factors driving the abundance and diversity of foraminifera in mudflat habitats. Three different trophic strategies were deduced for the foraminifera investigated in this study: Ammonia sp. T6 has an opportunistic strategy and is feeding on bacteria, nematoda, fungi, and diatoms when abundant; Elphidium oceanense is feeding mainly on diatoms, mixed with other preys when they are less abundant; and Haynesina germanica is feeding almost solely on medium‐large pennate diatoms. Although there are limitations due to the lack of species coverage in DNA sequence databases and to the difficulty to compare morphological and molecular data, this study highlights the relevance of combining molecular with morphological tools to study trophic interactions and microbiome communities of protists at the single‐cell scale.